Pemberdayaan UMKM Arang Briket Tempurung Kelapa bagi Masyarakat Desa Negara Agung Lampung Utara - Eka Yuniasih; Apriza; Ardian Saputra; Ari Almansyah; Arif Bagas Sanjaya; Binti Maulina; Cahyani Wulandari; Chesia Afriza; Chintia Anggraini; Muhammad Amir Syuhada (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
Indonesia, as one of the largest coconut producers in the world, continues to face challenges in optimizing the economic potential of coconut shell waste, which is often discarded or used as low-value traditional fuel. In Desa Negara Agung, Lampung Utara, this issue is also evident, while the community simultaneously struggles with limited knowledge of production techniques, managerial capacity, and digital marketing strategies for developing coconut shell briquette enterprises. This community service activity, implemented through the Community Service Program (KKN), aimed to empower local MSMEs by transforming coconut shell waste into high-quality, eco-friendly briquettes. The program was grounded in empowerment theory and the Asset-Based Community Development (ABCD) approach, emphasizing active participation and utilization of local resources. Methodologically, it applied Participatory Action Research (PAR) with stages of problem identification, planning, action, evaluation, and reflection. The findings demonstrate improvements in briquette production skills, innovations in hygienic and attractive packaging, and the adoption of digital marketing platforms. These outcomes indicate that the program not only enhanced the economic capacity of local MSMEs but also supported environmental sustainability through the productive use of coconut shell waste.